Valuation of Pražská plynárenská, a.s. - Kratochvíl, Jan; Hnilica, Jiří, 1976-; Kudela, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2014)
The goal of this thesis is to determine value of the distributor and supplier of natural gas Pražská plynárenská, a.s. as of December 31, 2013. The thesis is divided into two parts - theoretical and practical part. The theoretical part describes the processes and methodology of valuation, while the practical part applies described processes. The practical part starts with a description of the valued company and its business environment, followed by strategic and financial analysis, followed by a financial plan and valuation itself. The valuation is based on the discounted cash flows to entity method. The results from the discounted cash dlows method are further compared to the value based on industry multiplies. The thesis is concluded with discussion and explanation of the estimated value.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses